2022
DOI: 10.1101/2022.12.10.519872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive Evaluation of Rapamycin’s Specificity as an mTOR Inhibitor

Abstract: Rapamycin is a macrolide antibiotic that functions as an immunosuppressive and anti-cancer agent, and displays robust anti-ageing effects in multiple organisms including humans. Importantly, rapamycin analogs (rapalogs) are of clinical importance against certain cancer types and neurodevelopmental diseases. Although rapamycin is widely perceived as an allosteric inhibitor of mTOR (mechanistic target of rapamycin), the master regulator of cellular and organismal physiology, its specificity has not been thorough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Rapamycin is a bacterial macrolide initially used as an antifungal agent. However, due to its inhibitory effect on mTOR signaling, it is widely used as an autophagy inducer agent [24]. Activation of autophagy was confirmed using western blotting for assessment of LC3II/LC3I and p62 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapamycin is a bacterial macrolide initially used as an antifungal agent. However, due to its inhibitory effect on mTOR signaling, it is widely used as an autophagy inducer agent [24]. Activation of autophagy was confirmed using western blotting for assessment of LC3II/LC3I and p62 levels (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rapamycin is a bacterial macrolide initially used as an antifungal agent. However, due to its inhibitory effect on mTOR signaling, it is widely used as an autophagy inducer agent [24].…”
Section: Rapamycin Induces Autophagy In Primary Cortical Neuronsmentioning
confidence: 99%
“…To investigate whether this mTORC1-dependent gene expression program depends on the presence of the Rags, we performed RNA-seq experiments and tested the expression of selected target genes for each of these TFs, comparing WT and RagA/B KO HEK293FT cells. As a control, we also re-analysed our recently published RNA-seq dataset from Rapamycin-vs. DMSO-treated HEK293FT cells, in which mTORC1 is inhibited and S6K is dephosphorylated 59 . These analyses showed that selected SREBP, HIF1 and ATF4 target genes were consistently downregulated upon mTORC1 inhibition with rapamycin, confirming that the activity of these TFs is regulated downstream of mTORC1 (Ext.…”
Section: Lysosomal and Non-lysosomal Mtorc1 Complexes Regulate Differ...mentioning
confidence: 99%
“…To assess mRNA expression of selected SREBP, HIF1, ATF4, and TFEB target genes, we used two RNA-seq datasets: from rapamycin-or DMSO-treated HEK293FT cells (described in 59 ; NCBI Sequence Read Archive PRJNA872474), and from RagA/B KO versus control HEK293FT cells. Target genes of each transcription factor were retrieved using the Harmonizome 3.0 online platform (https://maayanlab.cloud/Harmonizome/) 105 .…”
Section: Gene Expression Analysismentioning
confidence: 99%